THE TRANSNATIONAL SUCCESS OF COSMOPOLITAN MAGAZINE - Ekawati Marhaenny Dukut (Universitas Gadjah Mada, 2014)
Studying about an American popular culture product such as the Cosmopolitan magazine for American Studies’ scholars can no longer be framed in studying how it is operated within the U.S. only. Instead, a look at how it is being transferred across nation’s borders and how it is regulated in other nations become a concern also to scholars. Time and space is no longer a border for a world that is transnational, so global values that are being sold in the magazine’s advertisements are being made continually popular by inserting local ideas. How has Cosmopolitan successfully achieved its globality? The following article discusses on the transnational culture that Cosmopolitan and its magazine advertisement brings and howit has taken in the local to support the global.